Are telemedicine/telehealth services ethical? [Internet üzerinden yapilan saǧlik hizmetlerinin etik açidan incelenmesi] - (:unkn) unknown (My University, 2002)
The devolopment rate of technolgy has affects on our daily lifes. The things we couldn't even imagine doing 10 years ago are easily done today. Especially the development rate of communication technologies has brought newer projects in the health field. One of these projects is telemedicine/telehealth services. The internet has permitted physicians, other health care professionals, patients, and other consumers to quickly access medical information in unprecedented volume. In 1994 the number of consultations done by interactive video conference system in the United States were 2500 whereas in 1995 this number increased to 7000 and a year later this number became 20.000 and in 1997 it reached 40.000. Tele-homecare systems have a capacity to enhance the delivery of home health care and thereby increase the quality of care. Some examples of how this can be accomplished are, reducing number of visits to the emergency rooms, reducing unnecessary visits to physician's offices, avoiding unnecessary costly visits by health providers, providing education of the patient in early symptom management, and monitoring vital signs on a 24-hours basis, therefore providing a potential for early intervention and/or prevention of repeat hospitalization. However there are some disadvantages such as the privacy of the personel health information. The information on the virtual world has some risks of being stolen easily. And also there might be misunderstandings through internet between the patient and his or her physician. Moreover, when a patient is getting his or her prescription, he or she might need to hear moral boosting words from the physician. World Medical Association has two statements on the topic telemedicine, one in Marbella in 1992 and one in Tel Aviv in 1999. In these statements, it tells about the accountability and responsibilities of the physicians, role of the patient, quality of care and safety in telemedicine, and recommendations about using the telemedicine system. Although telemedicine system has great offerings in the health field, it brings some problems with it. Countries who will use the telemedicine system must have laws and technological foundations. Also they must have experienced medical staff.